Effects of flexible roughness elements on diffusion in a turbulent boundary layer - Quraishi, Ali Akhtar, author; Cermak, J. E. (Jack E.), author; Civil Engineering Section, Colorado State University, publisher (Colorado State University. Libraries, 1964)
Diffusion of ammonia gas from a line source within a turbulent boundary layer, formed by flexible roughness elements fixed on the floor of a wind-tunnel test section, was studied. The flexible roughness elements consisted of plastic strips (0.25 in. wide, 0.01 in. thick and 4 in. high) fastened to wooden strips with transverse spacing of one element per linear inch and a spacing in the direction of flow of one row every 2 in. They were arranged with their broad side facing the direction of wind. The free-stream ambient velocity was 20 ft./sec. The line source was placed at different locations and height within the boundary layer. The concentration field was divided into three zones according to the distance from the source and the boundary-layer thickness; an initial, an intermediate and a final zone. The experimental data was analyzed accordingly and a procedure for predicting approximate concentrations in similar cases is suggested. The effect of source elevation was studied and it was found that as the elevation of the source was increased, the concentration at ground level for a short distance from the source was lower than "ground-level" source. It increased to a peak value and then decreased asymptotically according to the law of attenuation for a source at the boundary.
CER64AAQ-JEC3.
June 1964.
Keywords: Atmospheric turbulence; Diffusion; Boundary layer